Modeling and implementation of photovoltaic modules for a DC-DC Boost Converter - Ghani, Z.A.; Safwanah Rosli, S.; Othman, H. (Penerbit Universiti Kebangsaan Malaysia, 2022)
A photovoltaic (PV) system is a renewable energy system intended to convert sunlight into the usable electricity. Due to the rapid world infrastructure development, the demand for electricity is increasing drastically. One of the promising energy resources is the PV. The required energy demand can be provided by the increase of PV system deployment. Thus, as part of the design, development and implementation of a new PV system, a system design simulation is essential. This is to ensure that the designed system works properly according to design specifications. For this reason, a PV mathematical model is necessary in the development process of the PV system especially in the MATLAB/Simulink software environment. With the developed PV model, the PV system design and simulation is made handy, thus escalates the future energy demand. This work describes the development of the PV mathematical model in the MATLAB/Simulink software environment based on the PV related equations. The equations are formed by the consideration of the equivalent circuit of PV cell. The developed PV model characteristics such as the Power-Voltage (P-V) and Current-Voltage (I-V) curves are obtained as the simulation output in MATLAB/Simulink. The obtained characteristics are compared to the actual PV model A 100W RNG-50D Renogy, as to verify the effectiveness and closeness of the developed PV model to the real PV module. In addition, in the simulation, a dc-dc boost converter is also designed and integrated with the PV model as to verify the PV module and capability as a PV power source. The simulation results with the dc-dc boost converter DC-DC integration have shown that the developed PV model is very effective to be used for the PV system simulation.